From Theory to Practice: Applying the Markowitz Model in Stock Portfolio Management under ESG - Zhou, Xintong (International Journal of Global Economics and Management, 2024)
The study consisted of a month-long simulated stock market operation focusing on the comprehensive analysis of equity portfolio creation and management. Against the backdrop of growing concern for environmental protection, the S&P 500 Net Zero 2050 Climate Transition ESG Index was deemed the appropriate benchmark for the portfolios due to the average level of risk tolerance of customers. The investigation began with an in-depth assessment of macroeconomic and sector conditions, followed by careful selection of securities using both fundamental and technical analysis techniques. The portfolio was then optimized using the Markowitz model and subsequently managed using a variety of strategies, including trading, monitoring, and rebalancing. The subsequent phase of the research involves a rigorous evaluation of performance utilizing various metrics including single-period returns and the Sharpe ratio. The study culminates in a reflective analysis of the overall investment project. Despite the portfolio’s underperformance against the benchmark, the project provides invaluable insights into the intricacies of stock market investment and portfolio management, accentuating the impact of market volatility and the significance of strategic asset allocation.